Harmonic Oscillators in CMOS—A Tutorial Overview - Pietro Andreani; Andrea Bevilacqua (IEEE Open Journal of the Solid-State Circuits Society, 2021)
The harmonic oscillator is a truly irreplaceable as well as ubiquitous analog integrated circuit. Starting from the basics of its CMOS implementation, we will discuss the phase noise of the harmonic oscillator in some detail, where the intrinsic large-signal operation mandates a time-variant analysis. This will be followed by a survey of the most popular design techniques enabling a low phase noise and a wide range of oscillation frequencies.